Uv-responsive screen-printed porous zno nanostructures on office paper for sustainable and foldable electronics - Ferreira, Sofia Henriques (2022)
The fabrication of low-cost, flexible, and recyclable electronic devices has been the focus of many research groups, particularly for integration in wearable technology and the Internet of Things (IoT). In this work, porous zinc oxide (ZnO) nanostructures are incorporated as a UV sensing material into the composition of a sustainable water-based screen-printable ink composed of car-boxymethyl cellulose (CMC). The formulated ink is used to fabricate flexible and foldable UV sensors on ubiquitous office paper. The screen-printed CMC/ZnO UV sensors operate under low voltage (≤2 V) and reveal a stable response over several on/off cycles of UV light exposure. The devices reach a response current of 1.34 ± 0.15 mA and a rise and fall time of 8.2 ± 1.0 and 22.0 ± 2.3 s, respectively. The responsivity of the sensor is 432 ± 48 mA W−1, which is the highest value reported in the literature for ZnO-based UV sensors on paper substrates. The UV-responsive devices display impressive mechanical endurance under folding, showing a decrease in responsivity of only 21% after being folded 1000 times. Their low-voltage operation and extreme folding stability indicate a bright future for low-cost and sustainable flexible electronics, showing potential for low-power wearable applications and smart packaging.